Pilot study of gene mutations associated with Lynch syndrome in Slovak patients with breast cancer - Krasničanová, L; Saade, R; Priščáková, P; Gbelcová, H; Kaľavská, K; Karaba, M; Benca, J; Mego, M; Repiská, V (Klinicka onkologie, 2023)
BACKGROUND: Lynch syndrome (LS) is an autosomal dominant inherited disorder which causes an increased risk of cancer, especially colorectal and endometrial carcinomas. Recent studies have shown an association between LS and breast cancer as well. The aim of our study is to highlight the possible presence of mutations in genes associated with LS in patients with breast cancer and the need to include the examination of Lynch-associated genes in patients with a family history of breast cancer as well as in patients with recurrent breast cancer, as well as with the occurrence of other Lynch-associated cancer. MATERIALS AND METHODS: We analyzed tumor tissue samples from 78 patients with primary breast cancer. Our samples were tested with a gene panel associated with the risk of developing breast cancer, while in our study we focused primarily on the occurrence of mutations in mismatch-repair genes. DNA isolated from tumor tissue was sequenced using next generation sequencing (NGS) and analyzed using the Ingenuity Variant Analysis tool. To confirm the germline mutation, we examined the patient's blood sample using NGS sequencing. RESULTS: As a result of our analysis, we managed to identify a mutation in the PMS2 gene in one patient's breast tumor tissue. The presence of this mutation indicates that the resulting cancer may be a consequence of LS. As for pathogenicity, this was probably a pathogenic variant, as we detected deletions in the exon region, which led to frameshift mutation. Moreover, we also identified single-nucleotide pathogenic variants in the TP53 and PIK3CA genes. To definitively establish the diagnosis of LS in the patient, we examined a blood sample, where we also identified a mutation of the PMS2 gene. CONCLUSION: LS is underdiagnosed in many Lynch-associated cancers. However, in the case of a familial occurrence of breast cancer and other Lynch-associated genes, it is important to think about a possible diagnosis of LS and, if the patient meets the diagnostic criteria, to carry out a genetic examination of Lynch-associated genes.
Keywords: dědičné nepolypózní kolorektální nádory; Genetic Predisposition to Disease; Breast Neoplasms; MSH6; mismatch repair endonukleáza PMS2; MMR genes; MLH1; breast cancer; mutace; Neoplasm Recurrence, Local; oprava chybného párování bází DNA; lokální recidiva nádoru; Slovakia; Slovenská republika; ženské pohlaví; DNA Mismatch Repair; Mutation; Mismatch Repair Endonuclease PMS2; Humans; PMS2; MSH2; pilotní projekty; Pilot Projects; nádory prsu; Colorectal Neoplasms, Hereditary Nonpolyposis; Lynch syndrome; genetická predispozice k nemoci; zárodečné mutace; Female; Germ-Line Mutation; lidé